Aplicação do modelo de identificação e acumulação de resultados na gestão por unidade de negócio das sociedades de seguro - Mesquita, Emilene Faria (2012)
The Result Identification and Accumulation Model was conceptualized by Parisi (1995) for a coordinated range of activities that, inside a logical structure, collection, identify and accumulate data of several economic events from on organization. In this research, the model was developed to meet insurance companies.The aim of this study was to describe and analyze the premise of the Result Identification and Accumulation Model applied to Insurance Companies, allowing to obtain the results by Line of Business, identifying those that generate higher or lower benefits and enabling the improvement of its processes and better results. The deductive method was used for the study the conceptual literature of Economic Management, through the collection of data in documents used as primary sources and the inductive method as the study sample, by applying a questionnaire, achieving 12 insurance companies representing almost 80% of the Gross Written Premium in 2010 across the industry. It was evidenced through the questionnaire that the insurance companies do not use information as best as possible and the economic result is not main performance measure and often this result is not known by Line of Business. It was also evidenced that most insurance companies consider that the volume of premiums written as decision factor, contrary to the theory of Economic Management, which has the main factor as the economic result. Finally the Result Identification and Accumulation Model is examined through secondary data obtained from the Statistics Generator System of SUSEP Superintendência de Seguros Privados, concluding the sustainability of model for the insurance companies and academic contribution of this research in an original way for the segment